Public Awareness in The Use of Public Transportation Services in The City of Bandung - Ridwan Setiawan; Abdul Azis Wahab; Prayoga Bestari (Department of Civic Education, 2021)
Public awareness is one of the most important parts of a city development process. This awareness is part of the form of public response to a policy. One of them is the use of bus transportation. The purpose of this study is to describe the level of public awareness in using public transportation services, especially DAMRI buses. Also, to find out the role of the Bandung branch of the DAMRI branch. The research is motivated by the level of congestion that is increasing every year, and the use of city buses as public transportation in the city of Bandung is decreasing. The approach used is a qualitative approach with a case study method, and data collection techniques use observation, interviews, documentation, and literature studies. The results showed that the level of public awareness in the use of public transportation services in Bandung was still lacking because the awareness that arises from each person can change according to his conditions and environment. Lack of public understanding of facility utilization, also the lack of attractiveness of service providers is one of the factors influencing the use of public transportation. This requires the role and encouragement of various parties, namely the City Government, City and Provincial Transportation Office, Bandung Branch of Perum DAMRI, the community, and other parties together, as an effort to raise public awareness of the use of public transportation services in Bandung